2015
DOI: 10.1017/cjn.2015.281
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Outcomes of Traumatic Brain Injury from Biking Accidents With or Without Helmet Use

Abstract: Objective: To determine if health outcomes and demographics differ according to helmet status between persons with cycling-related traumatic brain injuries (TBI). Methods: This is a retrospective study of 128 patients admitted to the Montreal General Hospital following a TBI that occurred while cycling from 2007-2011. Information was collected from the Quebec trauma registry and the coroner's office in cases of death from cycling accidents. The independent variables collected were socio-demographic, helmet sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
1
20
0
3
Order By: Relevance
“…Helmets are the most discussed piece of concussion-related protective equipment, and they reduce the risk of moderate to severe brain injury in cycling. 57 However, the literature is not clear on their ability to prevent concussion in contact-sport athletes. 58 Ongoing research is targeting the development of helmet materials that may reduce the concussion risk.…”
Section: Community Levelmentioning
confidence: 99%
“…Helmets are the most discussed piece of concussion-related protective equipment, and they reduce the risk of moderate to severe brain injury in cycling. 57 However, the literature is not clear on their ability to prevent concussion in contact-sport athletes. 58 Ongoing research is targeting the development of helmet materials that may reduce the concussion risk.…”
Section: Community Levelmentioning
confidence: 99%
“…El uso de casco en ciclistas lesionados en México fue significativamente menor que lo reportado previamente en Alberta o Montreal(Canadá), donde el 26% de las personas fallecidas y el 25% de los ciclistas que presentaron TCE, respectivamente, lo llevaban puesto 13,14 . El casco es una intervención dirigida a la protección del ciclista.…”
Section: Discussionunclassified
“…On the other hand, they found that helmeted cyclist had a higher risk of polytrauma. 9 Many studies still confirm the protective effects of helmets in the case of head and face injuries. [28][29][30] Amoros et al claimed that cyclists with helmets were more frequently involved in collisions with pedestrians or bicycles and had a higher appearance of coexisting injuries in regions other than the head and face, which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 But on the other hand, there is no association between helmet use and the risk of facial injuries. Also, they do not protect the lower facial region.…”
mentioning
confidence: 99%